2016
DOI: 10.1074/jbc.m116.739458
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of Desmoglein 2 Is a Regulator of Assembly Dynamics and Protein Turnover

Abstract: Desmosomes are prominent adhesive junctions present between many epithelial cells as well as cardiomyocytes. The mechanisms controlling desmosome assembly and remodeling in epithelial and cardiac tissue are poorly understood. We recently identified protein palmitoylation as a mechanism regulating desmosome dynamics. In this study, we have focused on the palmitoylation of the desmosomal cadherin desmoglein-2 (Dsg2) and characterized the role that palmitoylation of Dsg2 plays in its localization and stability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 48 publications
5
38
2
Order By: Relevance
“…Our unbiased AP-MS experiments uncovered a new role for DHHC5 in cell adhesion. Palmitoylation regulates several proteins involved in cell:cell and cell:matrix adhesion (Little et al, 1998;Roberts et al, 2014;Lievens et al, 2016;Roberts et al, 2016;Aramsangtienchai et al, 2017) and for many of them, palmitoylation regulates their localisation. Among cell adhesion complexes, desmosomes are notable for the number of proteins in the complex that are palmitoylated, with at least 6 members of the complex palmitoylated in A431 cells (Roberts et al, 2014), and in this work, we have shown that DHHC5 is the PAT responsible for the palmitoylation of the key complex members desmoglein-2 and plakophilin-3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our unbiased AP-MS experiments uncovered a new role for DHHC5 in cell adhesion. Palmitoylation regulates several proteins involved in cell:cell and cell:matrix adhesion (Little et al, 1998;Roberts et al, 2014;Lievens et al, 2016;Roberts et al, 2016;Aramsangtienchai et al, 2017) and for many of them, palmitoylation regulates their localisation. Among cell adhesion complexes, desmosomes are notable for the number of proteins in the complex that are palmitoylated, with at least 6 members of the complex palmitoylated in A431 cells (Roberts et al, 2014), and in this work, we have shown that DHHC5 is the PAT responsible for the palmitoylation of the key complex members desmoglein-2 and plakophilin-3.…”
Section: Discussionmentioning
confidence: 99%
“…Among these is the important desmosomal cadherin desmoglein-2 (DSG2, Figure 4d). DSG2 is a known palmitoylated protein (Roberts et al, 2016), where its palmitoylation regulates the localisation and trafficking of the protein to the plasma membrane. Because of this, we decided to investigate whether DHHC5 is the PAT responsible for DSG2 palmitoylation, so we performed an ABE assay on DHHC5 depleted HeLa cells and control siRNA treated cells (Figure 6a).…”
Section: Dhhc5/golga7b Regulates Desmosome Trafficking and Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that SH2/SH3 adaptor proteins are often involved in tyrosine kinase signaling, the interaction between these networks and desmosomes deserves increased attention. In addition to these novel pathways, our BioID analysis also highlights possible regulators of desmosome stability, such as a single palmitoyltransferase and thioesterase that are excellent candidates to mediate the palmitoylation of desmosomal proteins (49,50) .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate this might be due to differences in transfer to the western blot membrane, or PEG-mediated differences in exposure of the protein to antibodies or HRP. While the signal differences challenge the accuracy of the S-fatty acylation ratios, the APE still provides a reliable method to determine the qualitative measurement of S-fatty acylation states (Roberts et al, 2016), as well as a semi-quantitative comparative assay between different conditions (Nathan P. Westcott, In Press; Yokoi et al, 2016). …”
Section: Commentarymentioning
confidence: 99%